The association of PTSD with physical and mental health functioning and disability (VA Cooperative Study #569: the course and consequences of posttraumatic stress disorder in Vietnam-era Veteran twins) - Goldberg, Jack (Qual Life Res, 2013)
PURPOSE: To assess the relationship of posttraumatic stress disorder (PTSD) with health functioning and disability in Vietnamera Veterans. METHODS: A cross-sectional study of functioning and disability in male Vietnam-era Veteran twins. PTSD was measured by the Composite International Diagnostic Interview; health functioning and disability were assessed using the Veterans RAND 36-Item Health Survey (VR-36) and the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0). All data collection took place between 2010 and 2012. RESULTS: Average age of the 5,574 participating Veterans (2,102 Vietnam theater and 3,472 non-theater) was 61.0 years. Veterans with PTSD had poorer health functioning across all domains of VR-36 and increased disability for all subscales of WHODAS 2.0 (all p < .001) compared with Veterans without PTSD. Veterans with PTSD were in poorer overall health on the VR-36 physical composite summary (PCS) (effect size = 0.31 in theater and 0.47 in non-theater Veterans; p < .001 for both) and mental composite summary (MCS) (effect size = 0.99 in theater and 0.78 in non-theater Veterans; p < .001 for both) and had increased disability on the WHODAS 2.0 summary score (effect size = 1.02 in theater and 0.96 in non-theater Veterans; p < .001 for both). Combat exposure, independent of PTSD status, was associated with lower PCS and MCS scores and increased disability (all p < .05, for trend). Within-pair analyses in twins discordant for PTSD produced consistent findings. CONCLUSIONS: Vietnam-era Veterans with PTSD have diminished functioning and increased disability. The poor functional status of aging combat-exposed Veterans is of particular concern.